Ewe Comic Heroes : Trickster Tales in Togo - Konrad, Zinta (Routledge library editions. Folklore ;, 2015)
The trickster character is prominent in the cultural, particularly narrative, traditions of many different peoples throughout the world. Comic and serious, stupid and clever, benevolent and evil, winner and loser, the trickster is a study in contradictions. The trickster cannot be pigeonholed, for he does not fit into any neat categories or definitions. This study, first published in 1994, aims to give the reader the opportunity to experience in some small measure the dynamic and exciting dramatic oral narrative performances of the Ewe people of West Africa.